Pengaruh Perpustakaan Keliling Terhadap Minat Baca Di Kecamatan Palaran Tahun 2018 - Roni Choirudin (ADMINISTRASI PUBLIK, 2018)
RONI CHOIRUDIN (141110013509203) "The Influence of the Mobile Library Against Reading Interest in Palaran District in 2018". Under the guidance of Prof. Dr. FI. Sudiran, M.So as Advisor I, Drs. Jamil Bazarah, M.Si As Advisor II One of the problems faced by mobile libraries is how they can serve people who are hungry for information with limited collections in limited service time. Thus the rapid rate of information, mobile libraries must play a more active role in disseminating the information in various forms, especially information in the form of books. Therefore the selection of mobile library collections must be truly professional. The type of research in this research proposal is quantitative. Quantitative research has a positivism perspective, which states that the existence of social reality / reality and physical reality. Therefore anyone who will examine the reality can observe / measure it. There is an influence of mobile library services in East Kalimantan Province library agencies on reading interest in Palaran District. From the calculation can be obtained that the calculated r value of 1.00 figures the correlation index is not negative, this means that the correlation between variable X (mobile library service) affects the variable Y (students' reading interest) and there is a direct relationship, with the word others have a positive influence between the two variables. So that the alternative Hypothesis (Ha) tells that there is a significant positive influence between mobile library services and students 'reading interest, and the null hypothesis (Ho) which states that there is a significant positive influence between mobile library services and students' reading interest is rejected. The number of mobile library services in the East Kalimantan Province library agency for reading interest services is 0.98, which means that this number is in the range of 0.90-1.00 with a positive correlation between variables X and variable Y including a very high correlation.